Code-switching as a teaching and learning strategy in mathematics classes : a case of Sekgosese East Circuit schools - Molotja, Tsebe Wilfred (My University, 2008)
The Department of Education language policy states that all official languages may be used in the teaching and learning at South African schools. The department of Education has adopted an Additive Multilingualism as an approach to teaching. English is however, still being used as the language of learning and teaching, even to the learners who are not mother-tongue speakers of the language. This study explores the question of whether code-switching aids or impedes teaching and learning in Mathematics. The problem arises when learners encounter concepts in Mathematics which are written in English and need to be explained in English. Learners often struggled to understand these concepts with the results that educators resort to using their home language to try to explain what these concepts mean. To understand the nature of this problem and how it affects teaching and learning, a qualitative research was undertaken. Two secondary schools in the Sekgosese East Circuit were purposefully sampled for this study. The purpose of the study was to explore the role of code-switching in the teaching and learning of concepts in Mathematics and its effects on the acquisition of Mathematics. The findings revealed that the school were code-switching was applied performed better in Mathematics than the school where code-switching was not employed. The study recommended that educators should use the learners’ home language in instances where their knowledge of English impedes them to convey the meaning clearly.
Thesis (M.ED.) --University of Limpopo, 2008
Keywords: Language policy; Mathematics teaching and learning; 370.1175044; Code switching (linguistics)